Management of myocardial infarction and the post-infarction patient - Ahmad H. Asdie, Ahmad H. Asdie (Universitas Gadjah Mada, 1992)
Acute myocardial infarction is the most common form of premature death in the industrial world. Its early recognition and active intervention are becoming important in the light of recent advances, particularly the use of streptokinase shortly after the onset of the infarct. Cardiopulmonary resuscitation (CPR) is important both inside and outside the hospital. General practitioners should be confident in performing both basic life support and advanced cardiac life support since the potential needs for resuscitation is becoming great.In semi-rural areas where the general practitioner is usually the first to be called for assistance, the use of advanced resuscitation and life support does save lives. The defibrillator is an essential piece of equipment for monitoring, diagnosis, management and treatment in these cases.Following myocardial infarction the family physician has a major role to play in rehabilitation and tertiary prevention by prescribing beta-blockers, starting within two weeks of the infarct.Key Words: myocardial infarction - premature death - CPR - streptokinase - defibrillator